A Standardized Extract of Lentinula edodes Cultured Mycelium Inhibits Pseudomonas aeruginosa Infectivity Mechanisms - Tena-Garitaonaindia, Mireia; Ceacero-Heras, Diego; Montoro, María Del Mar Maldonado; de Medina, Fermín Sánchez; Martínez-Augustin, Olga; Daddaoua, Abdelali (Frontiers in Microbiology, 2022)
The priority pathogen list of the World Health Organization classified Pseudomonas aeruginosa as the second top critical pathogen. Hence, the development of novel antibacterial strategies to tackle this bacterium is highly necessary. Herein we explore the potential antibacterial effect of Standardized extract of cultured mycelium of Lentinula edodes (AHCC®) on P. aeruginosa. AHCC® was found to inhibit the growth rate and biofilm formation of strain PAO1. No change in swarming was observed, but AHCC® hampered swimming and twitching motility. In accordance, a decreased expression of metabolism, growth, and biofilm formation genes was shown. AHCC® also diminished the levels of exotoxin A and bacteria inside IEC18 cells and the secretion of IL-6, IL-10 and TNF by infected macrophage. This effect was related to a reduced phosphorylation of MAPKs and to bacteria internalization. Taken together, data suggest that AHCC® has a potential role in the prevention and may be a useful component of food cocktails to prevent P. aeruginosa infections and may lead to the development of new therapies.